Structural Plasticity Induced by Ketamine in Human Dopaminergic Neurons as Mechanism Relevant for Treatment-Resistant Depression. (April 2019) - Collo, Ginetta; Cavalleri, Laura; Merlo Pich, Emilio
The mechanisms underlying the antidepressant effects of ketamine in treatment-resistant depression are only partially understood. Reactivation of neural plasticity in prefrontal cortex has been considered critical in mediating the effects of standard antidepressants, but in treatment-resistant depression patients with severe anhedonia, other components of the affected brain circuits, for example, the dopamine system, could be involved. In a recent article in Molecular Psychiatry, we showed that ketamine induces neural plasticity in human and mouse dopaminergic neurons. Human dopaminergic neurons were differentiated from inducible pluripotent stem cells for over 60 days. Mimicking the pharmacokinetic exposures occurring in treatment-resistant depression subjects, cultures were incubated with either ketamine at 0.1 and 1 µM for 1 h or with its active metabolite (2R, 6R)-hydroxynorketamine at 0.1 and 0.5 µM for up to 6 h. Three days after dosing, we observed a concentration-dependent increase in dendritic arborization and soma size. These effects were mediated by the activation of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor that triggered the pathways of mammalian target of rapamycin and extracellular signal-regulated kinase via the engagement of brain-derived neurotrophic factor signaling, as previously described in rodent prefrontal cortex. Interestingly, we found that neural plasticity induced by ketamine requires functionally intact dopamine D3 receptors. These data are in keeping with our recent observation that plasticity can be induced in human dopaminergic neurons by the D3 receptor-preferential agonist pramipexole, whose effect as augmentation treatment in treatment-resistant depression has been reported. Overall, the evidence of pharmacologic response in human inducible pluripotent stem cell-derived neurons could provide complementary information to those provided by circuit-based imaging when assessing the potential response to a given augmentation treatment.